Peripheral neuropathy as a unique manifestation of microscopic polyangetis in high altitude. Case report - Roque-Poma, Malena (2020)
Microscopic polyangiitis is a small vessel vasculitis whose incidence is 4 per 1 000 000 inhabitants, frequently associated with manifestations of rapidly progressive glomerulonephritis and pulmonary capilaritis, and a less frequent neurological involvement. The diagnosis is confirmed with a positive serology for antineutrophil cytoplasmic antibodies (ANCA) and specificity for fluorescence pattern perinuclear (P-ANCA) and myeloperoxidase (MPO). The ideal treatment is a combination of glucocorticoids and immunosuppressants. The case is presented of a 69-year-old patient with microscopic polyangiitis who debuts with peripheral neuropathy as the only manifestation, an atypical feature. The suggestion is made that in the presence of an isolated peripheral neuropathy, studies should be done to rule out the presence of Microscopic Polyangiitis, given its great variability in clinical presentation and potential treatments.